PENGELOLAAN BIMBINGAN DAN KONSELING DI SEKOLAH MENENGAH ATAS - Mulyati Mulyati (Manajer Pendididikan, 2020)
This qualitative study described the guidance and counseling planning in Kepahiang 2 High School. The results found that that the guidance and counseling program at Kepahiang 2 State High School was planned in advance, before the service was carried out by curriculum representatives who distributed foster students for each guidance and counseling teacher, according to a predetermined number.